Aplikasi Imkan al-Ru'yah Perspektif Fiqih dan Astronomi di Indonesia - Muhammad Hasan (AL-TAHRIR, 2013)
Abstract: One moderate method to determine the beginning of the month is imkān ar-ru’yah. On the other hand, there is no agreed imkān ar-ru’yah criteria among Muslims resulting in the claims of syar’i crescent and astronomy crescent. Therefore, Muslim scholars suggest that imkān ar-ru’yah criteria should be developed using a systematic scientific research. In addition, the atmosphere thickness in the equator is not similar to other countries so that the specific imkān ar-ru’yah criteria in Indonesia is possible to be different from other countries which are far from the equator. Based on the background, the writer is interested in to do research on imkān ar-ru’yah in Indonesia in the perspective of fiqh and astronomy. This writing uses “science cum doctrinaire approach”to analyse data . The findings of this research are as follows. First, in the fiqh perspective, there are several variables of imkān ar-ru’yah: calculating, horizon, crescent and testimony, and criteria. The imkān ar-ru’yah criteria in fiqh perspective is altitude >2˚ and elongation >3,6˚. Second, in the astronomy perspective, imkān ar-ru’yah criteria is formulated by altitudes >3,7˚ and elongation >5,5˚. Third, the tendency of the new moon criteria that is acceptable in the astronomy and fiqh perspectives is altitude >2,7˚ and elongation > 5,5˚.